A New Facial Homoleptic Tris‐cyclometalated Iridium(III) Complex with Oxygen‐bridged Triarylamine Units. Issue 15 (20th April 2020) - Zhang, Xinghua; Cao, Yibo; Song, Jialiang; Li, Kang; Jiang, Qibin; Yuan, Aihua; Shi, Chao
Abstract: A new facial homoleptic tris‐cyclometalated phosphorescent iridium(III) complex Ir(ppyNO)3 featuring three oxygen‐bridged triarylamine units has been synthesized via an efficient Suzuki–Miyaura cross‐coupling reaction of oxygen‐bridged triarylamine unit based boron reagent 1‐b with corresponding tribrominated iridium(III) complex Ir‐Br . It can not only show an effective green light emission, but also display a narrower full width at half maximum (FWHM=57 nm) and better solubility than that of the classical complex fac ‐Ir(ppy)3 (FWHM=82 nm, ppy=2‐phenylpyridine). Furthermore, a longer emission lifetime (τ=1201 ns) of Ir(ppyNO)3 in polystyrene (PS) film can be found than that (τ=45 ns) in CH2 Cl2 solution. In addition, the lowest triplet state (T1 ) of Ir(ppyNO)3 can exhibit both metal‐to‐ligand charge transfer ( 3 MLCT) and intraligand charge transfer ( 3 ILCT) excited state character according to DFT calculations. Abstract : A new facial homoleptic tris‐cyclometalated iridium(III) complex with oxygen‐bridged triarylamine units has been synthesized and it can not only show an effective green light emission, but also display a narrow full width at half maximum (FWHM=57 nm) and good solubility.